18.3k views
1 vote
Solve the following:
2(x+3)=x-4

1 Answer

5 votes

Answer:

x = -10

Explanation:

2(x + 3) = x + -4

Reorder the terms:

2(3 + x) = x + -4

(3 * 2 + x * 2) = x + -4

(6 + 2x) = x + -4

Reorder the terms:

6 + 2x = -4 + x

Solving

6 + 2x = -4 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.

6 + 2x + -1x = -4 + x + -1x

Combine like terms: 2x + -1x = 1x

6 + 1x = -4 + x + -1x

Combine like terms: x + -1x = 0

6 + 1x = -4 + 0

6 + 1x = -4

Add '-6' to each side of the equation.

6 + -6 + 1x = -4 + -6

Combine like terms: 6 + -6 = 0

0 + 1x = -4 + -6

1x = -4 + -6

Combine like terms: -4 + -6 = -10

1x = -10

Divide each side by '1'.

x = -10

User Trieu Nguyen
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.